Procedural and clinical outcomes of endovascular recanalization therapy in patients with cancer-related stroke. Issue 5 (October 2018) - Jung, Seunguk; Jung, Cheolkyu; Hyoung Kim, Jae; Se Choi, Byung; Jung Bae, Yun; Sunwoo, Leonard; Geol Woo, Ho; Young Chang, Jun; Joon Kim, Beom; Han, Moon-Ku; Bae, Hee-Joon
Objective: Embolism due to coagulopathy might be the main pathomechanism underlying cancer-related stroke (CRS). CRS patients with a large artery occlusion could be candidates for endovascular recanalization therapy (ERT), although its procedural and clinical outcomes are not well known. This study aimed to investigate the procedural and clinical outcomes of ERT in CRS patients and the characteristics associated with outcomes compared with those of conventional stroke patients. Methods: A registry of consecutive acute ischemic stroke patients who underwent ERT between January 2011 and October 2015 was retrospectively reviewed. CRS patients are described as those who had (a) cryptogenic stroke with advanced or metastatic cancer; (b) no other possible causes of stroke such as cardioembolism (CE) and large artery atherosclerosis (LAA); and (c) elevated D-dimer levels or diffusion-restricted lesions in multiple vascular territories. We compared procedural and clinical outcomes at discharge among CRS, CE, and LAA patients. Results: A total of 329 patients were finally enrolled in this study; of these, 19 were CRS patients. The rate of successful recanalization, defined as modified treatment in cerebral infarction grade 2b or 3, was lower in the CRS group than in the LAA and CE groups (63% versus 84% versus 84%, p = .06). CRS subtype was an independent predictor for successful recanalization after ERT in the multivariate analysis (odds ratio, 0.317; 95% confidence interval, 0.116–0.867; p < .001). No significant difference in the rate of good clinical outcomes at discharge was observed among groups. Conclusions: Although clinical outcomes at discharge were similar for CE and LAA patients, complete recanalization seemed more difficult to achieve in CRS patients than in conventional stroke patients.